不安定傾斜板上の立位姿勢保持能力における信頼性 - 村山, 敏夫; 尾山, 裕介; 太田, 玉紀 (体育測定評価研究, 2020)
In this study, we revealed the reliability of stability in a standing posture on an unstable tilt board that moves in all directions. 50 middle-aged and older people, consisting of 19 men (60.3±9.9 years) and 31 women (58.5±8.4 years). The subjects had their stability in a standing posture on an unstable tilt board for 20 seconds measured three times. We evaluated for the following four variables: all-direction stability index, all-direction average displacement, all-direction angle-change area, and total angle variation index. As a result, all of the evaluation variables except all-direction angle-change area for males showed a higher ICC in the second and third trials (men: 0.74-0.81, women: 0.73-0.79) than that in the first and second trials (men: 0.59-0.75, women: 0.69-0.77). Two-way ANOVA showed all of the evaluation variables were better for women than for men (p<0.05). Significant main effects were observed between the all-direction stability index and all-direction average displacement, and better for the third trial than the first trial (p<0.05). The number of trials in which the effect of practice appears was different between the evaluation variables, but the good reliability was ensured in the second and third trials for all of the evaluation variables. Therefore, it is suggested that the measurement method with the first trial as the practice trial and the second and third trial as the present trial was useful.